Killing Two Birds with One Stone: Selective Oxidation of Small Organic Molecule as Anodic Reaction to Boost CO2 Electrolysis. Issue 5 (13th October 2021) - Tian, Jianjun; Cao, Changsheng; Ma, Dong-Dong; Han, Shu-Guo; He, Yingchun; Wu, Xin-Tao; Zhu, Qi-Long
Abstract : Replacing anodic oxygen evolution reaction (OER) with the oxidation of small organic molecules in CO2 electrolysis is an ingenious strategy to reduce the energy consumption while produce valuable anodic products instead of low‐value O2 . Herein, an advanced CO2 electrolysis system constructed by replacing OER with selective methanol oxidation reaction (MOR) is reported as a proof‐of‐concept, which achieves the yielding of value‐added products in both cathode and anode. Notably, the MOR over a self‐supported NiCo‐based metal–organic framework‐derived anode (NiCo‐NF‐ET) only needs 1.291 V to reach a high current density of 100 mA cm −2, which is about 346 mV lower than that of OER. Simultaneously, formate can also be produced with the Faradaic efficiencies approaching to 100%. Consequently, in comparison with the conventional CO2 electrolysis system, integrating cathodic CO2 reduction reaction (CO2 RR) with anodic MOR can lead to the reduction of about 880 mV to deliver the current density of 30 mA cm −2, while without compromising the selectivity of the products in both electrodes. Herein, the great potential to increase the economic benefits of CO2 electrolysis via the rational design of nonprecious electrocatalysts and participated anodic oxidation reactions is shown. Abstract : A facile and economical CO2 electrolysis system is creatively constructed by replacing anodic oxygen evolution reaction with methanol oxidation reaction, in which the in situ NiCo‐MOF‐derived self‐supported anode is highly efficient and selective toward the conversion of methanol‐to‐formate with lower energy consumption, without compromising the performance of CO2 reduction reaction in cathode.